The effect of community-based health education programs on health literacy in severely impoverished counties in Southwestern China: Results from a quasi-experimental design - Li, Benyan; Huang, Yuan; Ling, Caitlyn; Jiao, Feng; Fu, Hongyun; Deng, Rui (Frontiers in Public Health, 2023)
Background A national health education program in impoverished counties to promote health literacy among rural populations was released by the Chinese government in 2018. Under this nationwide campaign, an integrated health education program was implemented in Yunnan province, which included additional culturally sensitive educational components for the severely impoverished prefectures. Objective This study examined the differential effects of the health education program models on health literacy outcomes among residents in poverty-stricken areas. Methods A quasi-experimental design was applied with two arms that included surveys at baseline (in October 2019) and endline (in June 2021) to collect a range of individual-level health information, including the Chinese Resident Health Literacy Scale. The intervention group received the national health education program with the additional Yunnan specific program; the control group received only the national program. Respondents were recruited via a multi-stage stratified sampling, including 641 participants at baseline (261 from the intervention sites and 380 from the control sites) and 693 participants at endline (288 from the intervention sites and 405 from the control sites). Chi-square and logistic regression analyses were performed to examine the association between program intervention and health literacy outcomes. Results The overall health literacy levels were low (1.87%) at baseline, and there was no statistically significant difference between two groups (1.92 vs. 1.84%, P = 1.000). A significant increase (from 1.87 to 11.11%, P < 0.001) in the health literacy level was observed at endline in both groups. The magnitude of increase was significantly greater in the intervention group relative to the control group (17.71 vs. 6.42%, P < 0.001). Adjusting for the confounding factors of individual and household characteristics, results from multivariate logistic regression revealed that the odds of having adequate health literacy among participants who received both the National Program and the Yunnan Program were 3.92 times higher than those who only received the National Program (95% CI: 2.10–7.33). Conclusion The findings highlighted the importance of incorporating non-verbal visual aids and culturally-sensitive media tools in health literacy education to address healthy lifestyle and the living contexts of the populations in poverty-stricken areas.